Redefining some genre-specific words: evidence from some English texts about Ashura - Fakhr-Rohani, M (2010)
The Battle of Karbala (Iraq) which took place on Ashura (10 Muharram 61 AH/ 10 October 680 AD) has since exerted some influences on Muslim communities. On such a day, Iman al-Husayn, the 3rd Infallible Iman and the youngest grandson of the Prophet Muhammad, was martyred, together with about 100 of his companions. As the religio-historical significance of the Ashura tragedy of Karbala has made it a symbol of true Islam, it has received the attention and devotion of Muslims, especially, the Shiites. Over time, concepts associated with the Ashura tragedy have become semantically polysemous and religiously (and sometimes regionally) culture-bound, hence somewhat untranslatable from such Islamicate langages as Arabic, Persian, and Urdu into English. A glance at some English publications about Islamic history (and early Shiite history in specific) reveals that the Ashura tragedy has had some linguistic influence on the English language. This influence is observable through a range of Ashura-oriented concepts and Oriental loan-words in English, e.g., Ashura, Muharram, taziya, and azadari (with the last one chiefly used in Indian English context). Certain collegiate English dictionaries seem to be in need of improvement about some Ashura-oriented concepts and senses. For example, words such as "Ashura" and "taziya" have several uses and meanings in Shiite English texts for which the definitions provided in Shorter Oxford English Dictionary (6th ed., 2007) are utterly insufficient. To fill this semantic-cum-lexicographical gap, some solutions can be envisaged, together with some practical ways, to upgrade major English dictionaries regarding typical Ashura discourse in English.